Registration of TIL:455, TIL:514, and TIL:642, three rice germplasm lines containing introgressed sheath blight resistance alleles - Pinson, S. R. M.; Oard, J.H.; Groth, D.; Miller, R.; Marchetti, M.A.; Shank, A.R.; Jia, M.H.; Jia, Y.; Fjellstrom, R.G.; Li, Z. (Wiley, 2008)
Three rice (Oryza sativa L.) germplasm lines designated as TIL:455 (Reg. No. GP‐112, PI 642943), TIL:514 (Reg. No. GP‐113, PI 642944), and TIL:642 (Reg. No. GP‐114, PI 642945) contain a total of eight novel alleles with sheath blight (caused by Rhizoctonia solani Kühn) resistance backcrossed into an elite U.S. rice genetic background having good grain quality traits, early maturity, and glabrous leaves and hulls. These three germplasm lines were jointly released in 2007 by the USDA‐ARS, the Louisiana State University Agricultural Center, and the International Rice Research Institute. The novel sheath blight resistance alleles contained in these lines originated from ‘TeQing’ (PI 536047), a high‐yielding rice cultivar from China that is well known in the United States for its strong resistance to sheath blight disease. With the aim of identifying improved germplasm suitable for introducing novel sheath blight resistance alleles into tropical japonica breeding programs, a combination of phenotypic and molecular data was used to select three lines from among 262 random backcross introgression lines.